2006
DOI: 10.1103/physrevlett.96.162701
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sub-Barrier Fusion Enhancement in theHe6+Pb206Reaction

Abstract: The fusion of 6He with 206Pb has been studied at energies close to and below the Coulomb barrier. The experiment was carried out at the Dubna Radioactive Ion Beams complex of FLNR, JINR. The 6He beam intensity was about 5 x 10(6) pps, the maximum energy being 60.3+/-0.4 MeV. The yield of the 210Po isotope, produced in the 2n-evaporation channel, demonstrates an extremely large enhancement of the sub-barrier fusion cross section as compared with the 4He+208Pb reaction. This enhancement is most likely due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 22 publications
6
67
2
Order By: Relevance
“…The experiment [4,5] performed in FLNR (JINR), Dubna in 2006 at the accelerator complex for radioactive beams DRIBs [12] confirmed the results on the enhancement of fusion close to the Coulomb barrier, when halo nuclei are involved. In this experiment the cross sections for the formation of compound nuclei as a function of energy were measured.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…The experiment [4,5] performed in FLNR (JINR), Dubna in 2006 at the accelerator complex for radioactive beams DRIBs [12] confirmed the results on the enhancement of fusion close to the Coulomb barrier, when halo nuclei are involved. In this experiment the cross sections for the formation of compound nuclei as a function of energy were measured.…”
Section: Introductionmentioning
confidence: 55%
“…Recently a series of experiments have been performed with the aim to study the fusion-fission process using 6 He beams with close-to-barrier energies [3][4][5][9][10][11]. However, the obtained data were rather controversial and showed that higher statistical confidence is necessary as well as more informative experiments giving possibilities of distinguishing different exit reaction channels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the pioneering work of J.J. Kolata and E.F. Aguilera [10][11][12] using the TWINSOL facility at Notre Dame (USA), additional measurements were carried out by R. Raabe [13,14] and R. Wolski [15] using the CRC facility at Louvain-la-Neuve (Belgium), and by Y.E. Penionzhkevich [16] and S.M. Lukyanov [17] using the radioactive beam facility at Flerov Laboratory of Nuclear Reactions (JINR, Dubna, Russia).…”
Section: Fusion and Reaction Cross Sectionsmentioning
confidence: 99%
“…A detailed study of the system 6 He+ 208 Pb was performed recently at CRCLouvain-la-Neuve in different experiments ( [3][4][5][6]). In these works the angular distribution of elastic and 4 He yields were measured in a range of energies around the Coulomb barrier (14,16,18,22 and 27 MeV). The angular distribution of the elastic cross sections relative to Rutherford at 22 MeV is shown in Fig.…”
Section: Angular Distributions Of Elastic and Alpha Yieldsmentioning
confidence: 99%